A unique cardiovascular presentation of Marfan syndrome. Issue 8 (9th June 2022) - Otero Luna, Andrea; Park, Kaylee B.; Schauer, Jenna; Castera, Mark; Quintana Grijalba, Carolina; Chikkabyrappa, Sathish Mallenahalli; Tjoeng, Yuen Lie; Romberg, Erin K.; Olson, Aaron; Glass, Ian A.; Young, Luciana
Abstract: We report a neonate with severe Marfan syndrome (MS), prenatally identified to have persistent atrial tachycardia, biventricular dysfunction, and an unusual structure within the atria. Detailed postnatal echocardiographic evaluation and cross‐sectional imaging confirmed congenital pseudoaneurysm of the mitral‐aortic intervalvular fibrosa. Emergent testing by next‐generation sequencing identified a FBN1 pathological variant, key to establishing goals of care. To our knowledge, this is the first reported case of a congenital pseudoaneurysm of the mitral‐aortic intervalvular fibrosa in MS.